2019
DOI: 10.1016/j.healthplace.2019.102148
|View full text |Cite
|
Sign up to set email alerts
|

Creating a dementia-friendly environment through the use of outdoor natural landscape design intervention in long-term care facilities: A narrative review

Abstract: There is an increasing volume of literature on the positive effects of outdoor natural landscapes on health and well-being. However, to date, there is a paucity of research on the effect of outdoor natural landscapes designed for people with dementia living in long-term care (LTC) facilities, in particular, those which have incorporated the characteristics of a dementia-friendly environment (DFE). This narrative literature review synthesizes current knowledge on the effect of outdoor natural landscape design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The results of greenness can be interpreted in two ways. First, urban greenness has been documented to be a protective factor against dementia and related mental health diseases (Motealleh et al, 2019). For example, Paul et al (2020) found that greenness could be negatively associated with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The results of greenness can be interpreted in two ways. First, urban greenness has been documented to be a protective factor against dementia and related mental health diseases (Motealleh et al, 2019). For example, Paul et al (2020) found that greenness could be negatively associated with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of population-based surveys such as the United Kingdom Census suggest the closer people live to the coast, the more likely they were to self-report good health, especially among more socio-economically deprived communities (Wheeler et al, 2012(Wheeler et al, , 2015. Such analyses are limited, however, in that they use area aggregates of both exposure and outcomes and are open to the critique of "ecological fallacy, " i.e., the mistake of making assumptions about individuals from group-based data.…”
Section: Bathing Waters Quality and Trendsmentioning
confidence: 99%
“…Marine and coastal ecosystems are part of a wider network of aquatic environments, including freshwater systems, which are generically referred to as "blue spaces" (White et al, 2010;Gascón et al, 2017). Despite the acknowledged interactions between healthy blue spaces and human health and well-being (Völker and Kistemann, 2011;Wheeler et al, 2012;Nutsford et al, 2016;Bullock et al, 2018), systematic research on this topic is relatively recent, and important knowledge gaps have been identified (Grellier et al, 2017;Fleming et al, 2019). These research gaps imply a weaker understanding of how marine blue spaces produce cultural and other relevant ecosystem services, how these are used, and their implications for human health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…For specific groups of older people, the methodology of age-friendly environments has also been subject to literature reviews focusing on the population with dementia living in long-term care facilities, to assess the effectiveness of the design of open and natural environments in improving the symptoms of dementia [27], and on older immigrants in community dwellings in terms of the factors that influence social inclusion [28].…”
Section: Summarising Existing Knowledge Regarding Age-friendly Citiesmentioning
confidence: 99%